Influence of Ni Loading on Catalytic Activity of NiO/g-Al2O3 for Hydrogenation of Coal Pyrolysis - Zhang, Lei; Shu, Xinqian; Zhang, Lei (Asian Journal of Chemistry, 2013)
Selecting g-Al2O3 as support, a series of nickel nitrate with different concentrations (5, 8 and 10 %) were prepared by incipient impregnation while the equivalent volume impregnation method was applied to prepare NiO/g-Al2O3 supported catalysts. XRD, TPR, XPS and SEM were used for characterization of these catalysts. The catalytic activity of NiO/g-Al2O3 increased with the nickel loading increasing in 400-800 ºC, but the catalytic activity of different loading NiO/g-Al2O3 had little difference in 900-950 ºC, the catalyst with 10 % load showed a good catalytic activity in whole pyrolysis process. The XRD characterizations of catalysts with different loadings showed that, 10 % loading had the highest catalysis activity, 8 % secondly and 5 % last, in the temperature range of 400-800 ºC. Therefore, it can be inferred that NiO acted as main catalyst during the reaction course. The SEM characterization of catalysts with different NiO loadings showed that the 10 % loading of active component Ni coarser crystalline grains was found. While distinct NiO crystals were analyzed by XRD. Therefore, it can be inferred that the coarse crystalline grains are NiO crystals, which were observed through SEM. The analytical result of SEM was consistent with the characterization results of XRD. The XPS with 10 % Ni loading inferred that existential form of Ni is NiO and NiAl2O4. On the specimen surface, the binding energy of Al2p is 74.00 ± 0.5 eV and the binding energy of O1s is 531.3 eV, which belong to the lattice oxygen in Al2O3. The value agreed well with the characterization results of XRD. The TPR analysis results indicate that the loading amount of NiO/g-Al2O3 is 9.12 %, which was very close to the theoretical data 10 %.